Innovative Strategies for Teaching Integers: A Systematic Literature Review - Ai Pin, Ng (Secholian Publication, 2025)
The instruction of integer has been one of the difficult mathematics education topics because of the current misconceptions and teaching gaps. This is a systematic literature review of research trends, pedagogical strategies, impact, limitations, and future directions of teaching integer operations that includes studies published after 2015. Twenty-one peer-reviewed articles were analysed with the help of the PRISMA model, and the usage of various innovative approaches, such as manipulative-based, contextual, model-based, technology-enhanced, and student-centred, was identified. These results prove that the number lines, manipulatives, and virtual tools are effective strategies to promote the conceptual learning and interest among students. Real life analogies and cultural elements provided contextual approaches that helped learners make learning relatable and the use of embodied learning and problem-posing activities enabled flexibility in reasoning. But problems like excessive use of tools, low sample sizes, little attention to multiplication and division, and teacher knowledge gaps were detected. Also, the ability to get students out of concrete thinking to abstract thinking is a critical challenge. This review highlights that there is a need to fill these gaps in future research that covers wider populations, longitudinal research, and teacher professional development. These points are consistent with the priorities of global education reform, which provides practical advice to educators, curriculum developers and policymakers on how to enhance the teaching of integers and help students develop mathematically.